BACTERIOLOGICAL PROFILE AND ANTIBIOTIC SUSCEPTIBILITY PATTERNS IN DIABETIC FOOT INFECTIONS, AT LADY READING HOSPITAL, PESHAWAR - Ullah, Irfan; Ali, Sobia Sabir; Ahmad, Ibrar; Khan, Muhammad Nawaz; ur Rehman, Mujeeb; Malik, Sajjad Ahmad (Journal of Ayub Medical College Abbottabad, 2020)
Background: Diabetic foot ulcer is one of the common complications of diabetes and is also the major cause of hospitalization across the world. To treat it properly, bacteriological profile is important to institute appropriate treatment. This study is done with the objective to determine the microbiological profile and antibiotic susceptibility patterns of organisms isolated from diabetic foot ulcers in Lady Reading Hospital, Peshawar Pakistan. Methods: This cross-sectional study was conducted from January to June 2019. Swab samples were collected from 114 patients with diabetic foot infections and inoculated on appropriate media. Antibiotic susceptibility tests were done by Kirby Bauer disk diffusion method. Results: E. coli were predominately isolated in the study, with ESBL in 41.6% of the cases. Strains of Pseudomonas with MDR and XDR were isolated in 21.8% and 6.25% of the patients respectively. Majority of Gram-positive isolates were Staphylococcus aureus, those were MRSA in 76.6% of samples. The commonly involved sites of DFU were the toes and forefoot, and the main causes were blister formation or trauma. Most of the patients were identified to have risk factors such as peripheral neuropathy, peripheral arterial disease, over weight and poorly controlled diabetes. Conclusion: In our study, Gram negative aerobes were predominantly isolated in the diabetic foot infections. A significant number of MDR isolates were also observed. Lack of awareness about DFU and inappropriate use of broad-spectrum antibiotics may be the main cause of increase in the frequency of MDR isolates. Keywords: Diabetic foot ulcer; Diabetic foot infections; Antibiotic susceptibility